Stakeholder Engagement for Improved School Policy: Development and Implementation - Avison, Claire (Can J Public Health, 2010)
The health and education departments of government share a responsibility for promoting the health of children through policies in the school setting. These policies can be enhanced through the involvement of such stakeholders as school personnel, students, parents or caregivers, health professionals, the non-profit sector and industry. Although there is little evidence-based literature on the roles of stakeholders in school policy development and implementation, stakeholder involvement appears to be critical throughout the policy process. This article discusses stakeholder involvement in the development and implementation of school policies that promote and support healthy eating and physical activity. Canadian examples illustrate stakeholder engagement in this context. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/BF03405621 and is accessible for authorized users.